MANAGEMENT 4.0 - López de Castro, Sandra (Revista Arbitrada Formación Gerencial, 2024)
The fourth industrial revolution involves a transformation towards the digitalization of production systems, characterized by the fusion of technology, automation and digitalization. Another characteristic is the great speed at which changes occur, driven by digital technological innovations, which offer a new way of creating, consuming and transforming services and products; all this aimed at the search for a better quality of life for the entire society, making it more efficient, rational and collaborative.